Utilization of Herbaceous Plants as Bioindicators of Air Pollution by Microscopic Observation - Misya, Meilyn; Prasetya, Johan Danu (Biospecies, 2024)
Air quality plays a crucial role in sustaining life and maintaining the balance of our planet. To monitor and maintain air quality, initiatives have been taken, such as using bioindicators. A research study was conducted to compare air quality in two different locations - the Mancasan Lor residential area and the east park area of Campus I UPN "Veteran" Yogyakarta. The researchers used Rhoe discolor plants and employed methods like literature study, sampling, and microscope observation in the laboratory. The study found that samples with more open stomata were indicative of better air quality in a preserved environment. This research highlights the importance of monitoring air quality to prevent environmental degradation and promote the wellbeing of ecosystems.